Ecologia da interação entre formigas, herbívoros e Ouratea spectabilis Engl. (Ochnaceae): condicionalidade nos resultados das associações dependente de variação geográfica e temporal uma discussão à luz da teoria dos mosaicos geográficos da coevolução de Thompson - Byk, Jonas (2010)
The herbivory is an important factor for the structuring and diversity of natural communities, and may be influenced by factors such as seasonality, and spatial interactions by plant-herbivores-predators. In response to herbivory plants have different defense strategies, mainly chemical, physical, phenological or biotic. The associations with ants, attracted by extrafloral nectaries (EFN), are probably the main biotic defenses of plants. This thesis aims to determine the variation over time, the benefits conferred by the ant EFN visitors from Ouratea spectabilis (Ochnaceae) in the Cerrado environment, against the action of herbivores if all species of ants actually protect the plant to receive extrafloral nectar and how the ants win by visiting extrafloral nectaries. We set up three experiments in isolation: one in which we manipulated in the laboratory, ants and plants with and without EFNS to measure the gain that the ants get in the extrafloral nectar as a food supplement. In the second chapter, we evaluated the performance of a species of ant (Cephalotes pusilus ) to see if all the species actually confer protection to plants with EFN and a final experiment, by the time spent and the exclusion of ants, we evaluated the interaction simultaneously for two years in Uberlândia - MG, Água Clara - MS and Brasilia - DF, in order to test the geographical mosaic theory of coevolution. We demonstrated for the first time, in an obvious way, that ants benefit by feeding on extrafloral nectar, increasing the weight and number of individuals in the course of a year. We showed that some ants, in this case Cephalotes pusilus do not confer protection to the plant and that just feed on nectar and pollen, showing that not all species behave aggressively and have features to protect the plant. In the final experiment, we could demonstrate that the interactions between ants and Ouratea spectabilis have the same ecological significance regardless of geographic region. It is suggested that one type of interaction is the result of coevolution, the set of interacting elements are subject to similar selective pressures that lead to interaction for the same outcome in this case, a mutualistic interaction, which corroborates the theory that was tested